Ethnomathematics in Dengklaq Games as a Media for Learning Mathematics in Sinunukan 1 State Junior High School - Suparni; Torang Siregar (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
Ethnomathematics is an instructional approach that establishes connections between cultural components and mathematical concepts inside educational settings. The incorporation of ethnomathematics-based learning holds significant importance in cultivating character values and nurturing children's appreciation for local culture, which has experienced neglect as a result of technological advancements. The objective of this study is to provide a comprehensive analysis of the mathematical components inherent in the conventional game of dengklaq. This study employs an ethnographic research methodology, utilizing a qualitative approach. This study centers on the Dengklaq gaming arena, the katuk players involved, the laws governing gameplay, and the Dengklaq players themselves. The employed methodologies for data collecting encompassed observation, interviews, field notes, and documentation. The present study used triangulation as a method of data analysis, encompassing the processes of data reduction, presentation, and drawing of findings. The research findings indicate the presence of mathematical components within the Dengklaq game, specifically in the realm of plane geometry, angle relationships (such as opposite angles, straight angles, and opposite angles), cube nets, the concept of reflection, mathematical logic, and the notion of probability.